Optisyenliğin Temelleri - Bayarı, Sevgi Haman; Alpaslan, Gökhan; Kurt, Havva Sibel; Kuru Mutlu, Hülya; Özünlü, Özgür; Doğruer, Semih; Köşe, Serap; Tombuloğlu, Semiha; Semercioğlu, Melike Güzin; Bilici, Sevim; Göcen, Tuğba; Erol, Mehmet Akif (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-